Experimental evidence of nonlinear avalanche dynamics of energetic particle modes. (1st June 2022) - Yu, L. M.; Zonca, F.; Qiu, Z. Y.; Chen, L.; Chen, W.; Ding, X. T.; Ji, X. Q.; Wang, T.; Wang, T. B.; Ma, R. R.; Yuan, B. S.; Shi, P. W.; et al.
Abstract: Recent observations in HL-2A tokamak give new experimental evidences of energetic particle mode (EPM) avalanche. In a strong EPM burst, the mode structure propagates radially outward within two hundred Alfvén time, while the frequency of the dominant mode changes self-consistently to maximize wave-particle power exchange and mode growth. This suggests that significant energetic particle transport occurs in this avalanche phase, in agreement with theoretical framework of EPM convective amplification. A simplified relay runner model yields satisfactory interpretations of the measurements. The results can help understanding the nonlinear dynamics of energetic particle driven modes in future burning plasmas, such as ITER.